A Micropropagation Protocol for the Endangered Medicinal Tree Prunus africana (Hook f.) Kalkman: Genetic Fidelity and Physiological Parameter Assessment - Komakech, Richard; Kim, Yong-goo; KIM, WOOK JIN; Omujal, Francis; Yang, Sungyu; Moon, Byeong Cheol; Okello, Denis; Rahmat, Endang; Nambatya Kyeyune, Grace; Matsabisa, Motlalepula Gilbert; Kang, Youngmin (Frontiers in Plant Science, 2020)
Prunus africana is an endangered medicinal plant and hence new propagation methods are urgently required to increase its populations. Unfortunately, propagation through seeds is challenging due to its long flowering cycle and recalcitrant seeds. We developed a protocol for micropropagation using nodal segment explants. A woody plant medium supplemented with vitamins, 15 g L-1 sucrose, and 1.0 mg L-1 6-benzylaminopurine supported the optimum rate (100%) of axillary shoot initiation. Supplementation with 15 g L-1 sucrose and 1.5 mg L-1 indole-3-acetic acid provided the optimum rate (75%) of root initiation. Rooted plantlets were successfully planted in sterilised horticultural soil containing perlite (2:1 v/v) and the survival rate was 98% following acclimatisation. The photosynthetic rate assessed using FlourPen FP110 series showed that the ratio of variable fluorescence to maximum fluorescence mean value for in vitro regenerated P. africana (0.830 ± 0.0008) was similar to that of the maternal P. africana plant (0.825 ± 0.005), indicating similarity in their photosynthetic performance; a pivotal process for growth and development. The Fourier transform near-infrared spectrometer analysis of the in vitro regenerated and the maternal P. africana plant samples exhibited homogeneity in the absorbance peaks at 8273, 6344, and 4938-4500 cm-1 associated with lipids, starch, and proteins. The genetic fidelity of regenerated plants was confirmed using the randomly amplified polymorphic DNA technique. Our protocol is suitable for use in large-scale P. africana to meet the increasing demands for it in the global market.